PENGARUH LINGKUNGAN KERJA DAN PEMBERIAN MOTIVASI TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU - Prihantanti, Aulia Dwi; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Human resources are a valuable asset for any organization due to their potential. This study aims to analyze how the work environment and motivation affect the performance of nurses at Taman Mental Hospital, Riau Province. This research used a quantitative survey method with a questionnaire as the data collection instrument for each variable. A sample of 117 nurses was randomly selected to provide a diverse picture and characteristics. Data analysis technique used multiple linear regression analysis. The results of this study revealed that both partially and simultaneously, the work environment and motivation have a positive and significant influence on the performance of nurses at Taman Mental Hospital, Riau Province, with a model influence of 66.8%, and the work environment is the dominating variable influencing the performance of nurses. This indicates that the work environment conditions at Taman Mental Hospital, Riau Province, meet acceptable conditions or even exceed their expectations. Keywords: work environment, motivation, nurse performance.